Our aim here is to remove the radicals from the denominator of each fraction and then to combine the terms into one expression.

First, we multiply top and bottom of each fraction with their respective denominators. This gives us a perfect square in the denominator in each case, and we can remove the radical.

`sqrt(frac{2}{3a}) - 2 sqrt(frac{3}{2a})`

` = sqrt(frac{2(3a)}{3a(3a)}) - 2 sqrt(frac{3(2a)}{2a(2a)})`

` = sqrt(frac{6a}{9a^2}) - 2sqrt(frac{6a}{4a^2})`

We then simplify and see that we have like terms (`sqrt(6a)`).

`= frac{1}{3a}sqrt(6a) - frac{2}{2a}sqrt(6a)`

`=frac{1}{3a} sqrt(6a) - frac{1}{a} sqrt(6a)`

We then proceed to subtract the fractions by finding a common denominator (`3a`).

`= frac{sqrt(6a) - 3sqrt(6a)}{3a}`

`=frac{-2sqrt(6a)}{3a}`

`=-frac{2}{3a} sqrt(6a)`

Please support IntMath!